Analysis of Animal Models of Traumatic Osteonecrosis of the Femoral Head Based on Blood Supply: A Literature Review - Linbao Wang; Yunzhuan Luo; Xing Qiu; Liangliang Cheng; Kaiming Ma; Jianchen Guan; Yuchen Liu; Jiawei Ying; Dewei Zhao (Orthopaedic Surgery)
ABSTRACT Traumatic osteonecrosis of the femoral head (TONFH) refers to ischemic osteonecrosis is resulting from an acute mechanical interruption of the blood supply to the femoral head. The early diagnosis and optimal treatment have been central focuses of research and continue to undergo improvement. Reliable animal models are essential for advancing research into the treatment of the disease. This review aims to provide a comprehensive overview of tetrapod models (rats, rabbits, dogs, and sheep) and bipod models (emus, ostriches), as well as various modeling methods (traumatic hip dislocation, dissection of the round ligament and ligature of the femoral neck, femoral neck fracture (FNF), reduction and internal fixation after femoral neck fracture, and highly selective disruption of the anterior‐superior retinacular vessels). This review examines the advantages, disadvantages, and applicability of each model. Based on blood flow analysis, it proposes a more reliable direction for TONFH modeling: simulating partial blood flow injury in the context of FNF.